(untitled) (LEARNing Landscapes, 2012)
Our definitions of creativity are varied and broad, ranging from the invention of small works to the achievement of global contributions. As arbitrary as they may be, our understandings generate stereotypical expectations for creative individuals and their behavior. I argue here that these expectations (from artistic work as a priori creative to originality as a criterion) may stand in the way of our appreciating children’s artistic development and their acquisition of the necessary tools and confidence to find and break boundaries. I urge teachers to be creative themselves in their interpretation and acceptance of children’s creative endeavors.